Peningkatan Hasil Belajar IPA Materi Ciri-Ciri Makhluk Hidup melalui Pembelajaran Kontekstual pada Siswa Kelas VI SD Negeri 2 Sidoharjo Polanharjo Klaten Semester I Tahun Pelajaran 2018/2019 - Sri Kinasih (Universitas Sebelas Maret, 2019)
The purpose of this study was to find out: (1) Implementation of contextual learning in science lessons material specific characteristics of living things in class VI SDN 2 Sidoharjo Polanharjo Klaten 2018/2019 academic year. (2) Student learning activeness during participating in contextual learning in science lessons material specific characteristics of living things in class VI SDN 2 Sidoharjo Polanharjo Klaten 2018/2019 academic year. (3) Student learning outcomes after participating in contextual learning on science lessons material specific characteristics of living things in class VI SDN 2 Sidoharjo Polanharjo Klaten 2018/2019? This type of research is Classroom Action Research (CAR), with research procedures: planning, action, observation, and reflection. Data collection techniques use: observation, interviews, and documentation. Based on the results of the study concluded: (1) The application of constextual learning to science subjects material specific characteristics of living things has gone according to the original plan, because the teacher is able to apply the learning to the best. (2) The application of contextual learning can increase the active involvement of students during learning. Students actively make observations outside the classroom, hold discussions or exchange ideas, and make presentations. Students also look happy and enthusiastic about learning. Learning tends to be centered on students, and teachers have more roles as motivators and facilitators. (3) The application of contextual learning is able to improve learning outcomes and student learning completeness. This is because this learning model can provide convenience to students to understand the subject matter, because students can exchange ideas and cooperate with friends.